Control of technical maintenance quality of manufactured articles of aviation technique - Бурлаков, В. И.; Ханан, Ясер; Мансур, Жихад (Proceedings of National Aviation University (archive), 1999)
Considered are principle errors of technical personnel in technical maintenance of aviation systems which result in aircraft flying accidents also their classification is proposed. Presented is the distribution of technical personnel errors depending on the investigated factors. Also offered is mathematical expression of estimation of aircraft reliability in flight depending on the quality of aircraft maintenance